Analisis Pemikiran Soekarno Dalam Perumusan Pancasila Pada Prinsip Ketuhanan - Putri Widia Ningsih; Yakobus Ndona (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Pancasila as the basis of the Indonesian state regulates the entire order of national and state life as well as all aspects of the state administration of the Unitary State of the Republic of Indonesia (NKRI). Pancasila did not appear suddenly, but through a long process in the history of the Indonesian nation with contributions from figures such as Prof. Mohammad Yamin S.H., Prof. Dr. Supomo, and Ir. Sukarno. Ir. Soekarno, as one of the founding fathers and explorers of Pancasila, popularized this ideology in his speech on June 1 1945, which became the main reference in the formulation of Pancasila. The process of formulating Pancasila involved various groups with different views, which Soekarno finally succeeded in synthesizing into five main principles: Nationality, Internationalism, Democracy, Prosperity and Belief in God. The principle of God, which was initially proposed as the fifth principle, was finally placed as the first principle in Pancasila. This research uses a literature study method to examine Soekarno's views regarding the principle of God and its relevance in the context of a country that is religiously and culturally diverse. The findings of this research show that Soekarno's thinking regarding God offers an inclusive vision that can unite various beliefs in one principle that is accepted by all Indonesian people, strengthen the nation's spiritual foundation, and help face the challenges of globalization and changes in societal values.